الرسائل الحربيّة في وقعة صفين مقاربة تداوليّة - حسين حيال, أحمد (Journal of College of Education, 2021)
In this research, we try to uncover the deliberative values contained in the war messages collected by Ibn Muzahem al-Munqari (T 212H) in his blog (Sifin Post), in which he collected all his correspondence, poetry and prose during and before the war The message receives its deliberative value from its contents for the purposes of the sender and its intended purpose, and the recipient's knowledge of the communication participants with the sender whether it is information accompanying the production of the message or presuppositions.
Keywords: الخطاب الحربي, الرسائل, الإخبار, الاستدلال.